Effects of DMI and strobilurin fungicide combinations on scab and powdery mildew incidence in apple production: a preliminary study - Holb, I. J.; Kocsis, M.; Kruppa, J.; Abonyi, F. (International Journal of Horticultural Science, 2016)
The aim of our study was to evaulate the effectiveness of four DMI and strobilurion fungicide combinations in a season-long disease management programme against apple scab and powdery mildew in two integrated apple orchards on cultivar Jonagold. The four spray programmes were: i) standard, ii) DMI dominant iii) strobilurin dominant, and iv) DMI and strobilurin dominant. Apple scab incidence as generally high in both orchards in the standard fungicide treatment plots ranged between 21.8 and 26.4%. Leaf scab incidence was higher in all treatments compared to fruit incidence. Scab incidence was generally higher at Mándok compared to Ófehértó. In both locations the lowest scab incidence was assessed in DMI dominant treatment ranged between 5 to 10.7%, which was not signifi cantly different from the DMI and strobilurin dominant treatment. Powdery mildew incidence was generally low in both orchards in all fungicide treatments ranged between 0.002 and 0.5%. Although there were no signifi cant differences among treatments, the lowest powdery mildew incidence was assessed in the DMI and strobilurin dominant treatment in Mándok and in the strobilurin dominant treatment in Ófehértó.